(untitled) (Revista Contexto & Educação, 2026)
This study analyzed the implementation of the National Training Program in Public Administration (PNAP) at the Federal Rural University of Pernambuco (UFRPE), based on the satisfaction perceptions of a group of graduating students from the Bachelor’s Degree in Public Administration (BAP) program. Given that public policy implementation involves multiple actors, interests, and contingencies, a comprehensive analytical framework encompassing macro, meso, and micro levels was proposed to analyze and define directions in the implementation process, situating the student experience within this context. Student satisfaction was examined across five institutional factors: virtual learning environment (VLE), tutors, professors, student support buildings, and course attributes. The data collected indicated satisfaction with the VLE, tutor performance, and the overall course structure, but also significant criticisms concerning faculty performance and the infrastructure of the student support buildings. Furthermore, weaknesses were identified in the articulation among teaching, research, and extension activities, deficiencies in instructional materials, and the absence of formative practices aligned with the objectives of the BAP. These results reflect the perceived effectiveness of the public policy, that is, the extent to which the formal objectives of the policy are achieved from the perspective of its direct beneficiaries. Based on these findings, the initial hypothesis was confirmed: student satisfaction is related to multiple levels of implementation and can provide important insights regarding the effectiveness of public policy. Consequently, the study highlights the importance of a multilevel approach as a tool for reflection and action, which can contribute to diagnosing shortcomings and identifying possibilities for correction and enhancement of the Program. The study concludes that student satisfaction constitutes a significant input in the evaluation process of educational policies. Although it is insufficient alone to assess policy effectiveness in a broad sense, student satisfaction surveys should be connected with other tools and data sources to inform diagnosis and program improvement. For future research, the inclusion of additional stakeholders, institutional documents, and complementary evaluation instruments is recommended to support decisions that generate concrete actions for the advancement of PNAP. Keywords: Public policy; implementation; effectiveness; student satisfaction; distance higher education.